the Evaluating Traditional Game-Based Instructional Strategies to Enhance Cognitive Skills in Physical Education Learning - Ubaedi Ubaedi; Rahmat Gunawan; Ilona Pratiwi Hutabarat; Doki Harpinus (Journal of Innovative and Creativity, 2026)
This study aimed to evaluate the effectiveness of traditional game-based instructional strategies in enhancing elementary school students’ cognitive skills in physical education (PE) learning. The research employed a quasi-experimental design with a pretest–posttest control group approach. The study was conducted in a primary school located in a mountainous area with limited access to digital learning resources, emphasizing the importance of contextual and low-cost instructional alternatives. The participants consisted of eighteen fourth- and fifth-grade students who were divided into an experimental group (n = 9) and a control group (n = 9). The experimental group received PE instruction integrated with traditional games, while the control group was taught using conventional instructional methods. Students’ cognitive skills were measured using a cognitive assessment instrument administered before and after the intervention. Data were analyzed using descriptive statistics, paired-samples t-tests, independent-samples t-tests, and normalized gain (N-Gain) analysis. The results indicated that both groups experienced significant improvements in cognitive performance; however, the experimental group demonstrated substantially higher learning gains. The experimental group achieved a mean gain of 12.56 (52.7%), compared to 7.67 (37.9%) in the control group. Inferential analysis revealed a statistically significant difference in posttest scores favoring the experimental group. These findings suggest that traditional game-based instructional strategies are effective in improving students’ cognitive skills in physical education learning, particularly in educational settings with limited technological resources.